Health care need and health disparities: Findings from the Regional South Australia Health (RESONATE) survey. (7th August 2020) - Leach, Matthew J.; Gillam, Marianne; Gonzalez‐Chica, David A.; Walsh, Sandra; Muyambi, Kuda; Jones, Martin
Abstract: Regional South Australia has some of the highest rates of psychological distress, chronic disease and multimorbidity of any Australian State or Territory. Yet, the healthcare needs of this population are still not completely understood. To better understand the healthcare needs of regional South Australians, we invited adults living in the region to complete the 44‐item consumer utilisation, expectations and experiences of healthcare instrument (CONVERSATIONS), online or in hard‐copy. The survey was conducted between April 2017 and March 2018. A multi‐modal recruitment campaign was utilised to promote the survey. We examined associations between study outcomes and remoteness area, and drew comparisons between our findings and other surveys reporting pertinent outcomes in the urban SA population. The questionnaire was completed by 3, 926 adults (52.5% females; 37.6% aged 60 + years). Among the 264 distinct health conditions reported by participants, the most prevalent were hypertension (31.6%), depression (25.7%), anxiety (23.5%) and hypercholesterolaemia (22.9%). The lifetime prevalence of these conditions among participants exceeded rates reported in urban SA. The largest regional‐urban health disparities were observed for eczema/dermatitis, skin cancer, other cancer types and cataracts, where prevalence rates were 2075%, 400%, 373% and 324% higher, respectively, than that reported in urban SA. Participants also reported higher levels of multimorbidity (37.7% higher) relative to urban South Australians. By contrast, participants appeared to be exposed to fewer lifestyle risk behaviours (e.g. smoking, alcohol, inadequate fruit or vegetable intake) than their urban counterparts. In summary, there was a high level of healthcare need, and considerable health disparity among participants when compared with urban settings (particularly for skin and eye conditions). These findings highlight the need for a more targeted approach to delivering health services and health promotion activities in regional areas.